Interpreting and implementing the IB Learner Profile in an internationalised school in China: a shift of focus from the ‘Profile as text’ to the ‘lived Profile’ - Poole, Adam (Sage, 2017)
This article presents findings from a case study that explored the way Sophie, an expatriate International Baccalaureate Diploma art teacher in an internationalised school in Shanghai, China, interpreted and implemented the International Baccalaureate Learner Profile. The findings challenge the view that the Profile exerts a regulatory force on teachers’ behaviour by showing that Sophie not only reshaped the Profile according to her beliefs about teaching and learning, but also resisted what she perceived to be underlying patriarchal and westernising discourses. Findings suggest that the notion of a regulatory discourse should focus on both the Profile as text and also what could be called the lived Profile. Finally, this article offers tentative recommendations for professional development that incorporate both the Profile as text and the lived Profile.